Law on State Compensation Liability - The National Assembly (2009)
This Law provides for the State's liability to pay compensation to individuals and organizations suffering from damage caused by official-duty performers in administrative management, legal proceedings and judgment enforcement activities; compensation procedures; the rights and obligations of individuals and organizations suffering from damage; compensation funds and the reimbursement liability of official-duty performers who have caused the damage.